Detection of Prostate Specific Membrane Antigen at Picomolar Levels Using Biocatalysis Coupled to Assisted Ion Transfer Voltammetry at a Liquid-Organogel Microinterface Array - Akter, R.; Arrigan, Damien (American Chemical Society, 2016)
A label-free electrochemical strategy for the detection of a cancer biomarker, prostate specific membrane antigen (PSMA), at picomolar concentrations without the use of antibodies, was investigated. The approach is based on the assisted ion transfer of protons, generated by a series of enzymatic reactions, at an array of microinterfaces between two immiscible electrolyte solutions (μ-ITIES). This nonredox electrochemical approach based on biocatalysis-coupled proton transfer at the μ-ITIES array opens a new way to detect the prostate cancer biomarker, with detection capability achieved at concentrations below those indicative of disease presence. The strategy is expected to contribute to cancer diagnostics, recurrence monitoring, and therapeutic treatment efficacy.